3D quantitative synthetic MRI‐derived cortical thickness and subcortical brain volumes: Scan–rescan repeatability and comparison with conventional T1‐weighted images. Issue 6 (10th April 2019) - Fujita, Shohei; Hagiwara, Akifumi; Hori, Masaaki; Warntjes, Marcel; Kamagata, Koji; Fukunaga, Issei; Goto, Masami; Takuya, Haruyama; Takasu, Kohei; Andica, Christina; Maekawa, Tomoko; Takemura, Mariko Yoshida; et al.
Abstract : Background: Previous quantitative synthetic MRI of the brain has been solely performed in 2D. Purpose: To evaluate the feasibility of the recently developed sequence 3D‐QALAS for brain cortical thickness and volumetric analysis. Study Type: Reproducibility/repeatability study. Subjects: Twenty‐one healthy volunteers (35.6 ± 13.8 years). Field Strength/Sequence: 3D T1 ‐weighted fast spoiled gradient recalled echo (FSPGR) sequence was performed once, and 3D‐QALAS sequence was performed twice with a 3T scanner. Assessment: FreeSurfer and FIRST were used to measure cortical thickness and volume of subcortical structures, respectively. Agreement with FSPGR and scan–rescan repeatability were evaluated for 3D‐QALAS. Statistical Tests: Percent relative difference and intraclass correlation coefficient (ICC) were used to assess reproducibility and scan–rescan repeatability of the 3D‐QALAS sequence‐derived measurements. Results: Percent relative difference compared with FSPGR in cortical thickness of the whole cortex was 3.1%, and 89% of the regional areas showed less than 10% relative difference in cortical thickness. The mean ICC across all regions was 0.65, and 74% of the structures showed substantial to almost perfect agreement. For volumes of subcortical structures, the median percent relative differences were lower than 10% across all subcortical structures, except for the accumbens area, and all structures showed ICCs of substantial to almost perfect agreement. For the scan–rescan test, percent relative difference in cortical thickness of the whole cortex was 2.3%, and 97% of the regional areas showed less than 10% relative difference in cortical thickness. The mean ICC across all regions was 0.73, and 80% showed substantial to almost perfect agreement. For volumes of subcortical structures, relative differences were less than 10% across all subcortical structures except for the accumbens area, and all structures showed ICCs of substantial to almost perfect agreement. Data Conclusion: 3D‐QALAS could be reliably used for measuring cortical thickness and subcortical volumes in most brain regions. Level of Evidence: 3 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;50:1834–1842.